1997
DOI: 10.1111/j.1399-6576.1997.tb04685.x
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of clonidine and dexmedetomidine across the isolated perfused human placenta

Abstract: Dexmedetomidine disappeared faster than clonidine from the maternal circulation, while even less dexmedetomidine was transported into the fetal circulation. This was due to its greater placental tissue retention, the basis for which probably is the higher lipophilicity of dexmedetomidine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(44 citation statements)
references
References 23 publications
3
38
0
3
Order By: Relevance
“…The results showed no difference in the Apgar score, heart rate or NACS compared with the control group. The α 2 -agonist clonidine was safely used as an intrathecal supplement in cesarean sections 34,35) ; however, dexmedetomidine eliminates faster than clonidine in maternal circulation and much less in fetal circulation, 36) thus, theoretically, dexmedetomidine is safer for babies than clonidine.…”
Section: )mentioning
confidence: 99%
“…The results showed no difference in the Apgar score, heart rate or NACS compared with the control group. The α 2 -agonist clonidine was safely used as an intrathecal supplement in cesarean sections 34,35) ; however, dexmedetomidine eliminates faster than clonidine in maternal circulation and much less in fetal circulation, 36) thus, theoretically, dexmedetomidine is safer for babies than clonidine.…”
Section: )mentioning
confidence: 99%
“…Dexometomedine has high lipophilicity and so it passes through placenta but it disappears very fast [44]. Mahdy et al, found that after intrathecal dexmedetomidine injection there were significantly longer sensory and motor block times than patients in control and fentanyl group and there were no adverse effects on mothers or babies in any group [45].…”
Section: Obstetric Usementioning
confidence: 99%
“…Os autores justificaram o aumento no tempo de sedação, embora tenha havido diminuição na meia vida de eliminação, pela menor ligação protéica do medicamento nestes pacientes. Ala-Kokko e col. 23 compararam a transferência placentária da dexmedetomidina e da clonidina em modelo experimental de cotilédones placentários humanos perfundidos. Houve maior retenção placentária da dexmedetomidina, diminuindo a exposição da droga do lado fetal.…”
Section: Farmacocinética E Farmacodinâmicaunclassified